Studio pilota del questionario sulle strategie di lettura «Dimmi come leggi» per il triennio della scuola secondaria di secondo grado e studenti universitari - Giusi Castellana; Pietro Lucisano (LED Edizioni Universitarie, 2021)
The study presents the factorial validity, using graphic organizers, controlling the process of the version of the questionnaire on reading strategies, «Tell me How to Read», aimed at the students of upper secondary school and university students. The dimensions investigated correspond to the 7 strategies already tested in the previous versions (lower secondary and primary school, Castellana, 2018, 2020a): identifying reading purposes, activating previous knowledge, making predictions, selecting main information, using graphic organizers and a scale on the self-perception of the difficulties. The new questionnaire consisting of 82 items, was linguistically revised and items that investigate more complex levels of the reading process were added. It was administered to a convenience sample of 543 students, attending the fourth and fifth grades of upper secondary school and Ist-IIIrd year students of the Sapienza University of Rome and Parma. The factor analysis of the questionnaire confirmed the 7 dimensional structure. The questionnaire reduced to 53 items was used within the OFA Italian course of the Department of Psychology at Sapienza University, as an instrument for metacognitive self-assessment of reading and as support for teaching understanding. The scores obtained by the students (99) on the QSL were correlated with the scores of the final test of the course. The value of correlation found between the tests and questionnaire is significant and equal to .377.